2012
DOI: 10.1287/msom.1110.0341
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of Patient Flows in the Cardiac Intensive Care Unit

Abstract: This paper explores the rationing of bed capacity in a cardiac intensive care unit (ICU). We find that the length of stay for patients admitted to the ICU is influenced by the occupancy level of the ICU. In particular, a patient is likely to be discharged early when the occupancy in the ICU is high. This in turn leads to an increased likelihood of the patient having to be readmitted to the ICU at a later time. Such "bounce-backs" have implications for the overall ICU effective capacity-an early discharge immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 34 publications
7
139
3
Order By: Relevance
“…Moreover, it is possible that the delay effects will be seen prior to 100% occupancy as some beds may be reserved in anticipation of patient arrivals from other hospital units, such as the Operating Room. This characterization of the ICU being busy is similar to the approaches taken in Kc and Terwiesch (2012), Kim et al (2012), Chan et al (2012) and Batt and Terwiesch (2012) among others. Note that we examined other measures of busy, including different thresholds and times at which the occupancy was measured.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Moreover, it is possible that the delay effects will be seen prior to 100% occupancy as some beds may be reserved in anticipation of patient arrivals from other hospital units, such as the Operating Room. This characterization of the ICU being busy is similar to the approaches taken in Kc and Terwiesch (2012), Kim et al (2012), Chan et al (2012) and Batt and Terwiesch (2012) among others. Note that we examined other measures of busy, including different thresholds and times at which the occupancy was measured.…”
Section: Resultssupporting
confidence: 77%
“…As we will see in our analysis of queueing systems with delay-dependent service times, this impact can be substantial. We note that prior work has demonstrated that when the ICU is busy, patient LOS may decrease (Kc and Terwiesch 2012). In their work, they focus on a single cardiac ICU where patients are cared for following cardiac surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The service time of each patient (irrespective of the mode of arrival) in the ED is exponentially distributed with mean m 1 (see Green and Nguyen 2001 for a discussion of this assumption) and that the length of stay of each patient (emergency as well as nonemergency) in the inpatient department is exponentially distributed with mean m 2 . Recent evidence suggests that length of stay might be dependent on the level of congestion in the inpatient department (Kc and Terwiesch 2012). We do not incorporate this effect to maintain analytical tractability.…”
Section: Unpredictable Variabilitymentioning
confidence: 99%